Investigating the effect of the family-centered empowerment model on the weight and self-concept of obese boys - Seyed Hossein Hosseini Motlagh; FatemehSadat SeyedNematollah Roshan; Farnaz Shishehgar (BMC Psychology)
Abstract Background Obesity in children is a chronic problem that can lead to physical and psychological complications, including changes in self-concept. Since the family plays an important role in children’s physical and mental health, it should be considered the central point in all healthcare interventions. This study was conducted to determine the effect of the family-centered empowerment model on the weight and self-concept of obese boys. Methods This research was a semi-experimental study with a pretest-posttest design and control group. The sample size consisted of 30 male students between the ages of 9 and 12, with a BMI greater than the 95th percentile in each group (test-control). The family empowerment program was implemented in 4 steps (perceived threat, self-efficacy, self-esteem, evaluation) and during 8 sessions (45 min for each). The data collection tools were a demographic profile questionnaire, a Pirez and Harris standardized self-concept questionnaire, and a digital weight scale. Data were analyzed using SPSS version 22 software. The significance level was considered P ≤ 0.05. Results The results of the study showed that the average score of self-concept in the control group did not change significantly over time(P = 0.762), while in the test group, the average score of self-concept immediately after the intervention and after 1.5 months compared to before the intervention showed a significant increase (P = 0.038). There were no significant changes in the mean weight (P = 0.780) and BMI (P = 0.867) before and after the intervention in the control group, but statistically significant changes were seen in the mean weight (P = 0.040) and BMI (P = 0.039) in the test group. Conclusions Implementing a Family-Centered Empowerment Model improved self-concept and weight management in obese primary school boys. These outcomes may contribute to positive lifestyle changes, such as increased physical activity, healthier eating habits, and maintaining a normal weight. Trial registration Not applicable.